A Triple Helix Model for Sustainable Community Empowerment: A Case Study of Orobulu Village - Umam, Muchammad Helmi; Fakhruddin, M. Anas (SIYAR Journal, 2025)
Sustainable rural development is a strategic issue that requires cross-stakeholder collaboration to optimize local potential. However, most studies still focus on sectoral interventions, neglecting the integration of universities, village governments, and local enterprises in a synergistic manner. This article proposes the application of the Triple Helix Model as a collaborative approach to strengthen village governance, enhance access to technology, and foster local economic empowerment. The study employs literature review and conceptual analysis to formulate a step-by-step implementation model relevant to rural contexts in Indonesia. The main contribution of this research lies in emphasizing the integration of academic knowledge, evidence-based village policies, and local entrepreneurial innovation within a sustainable framework. Accordingly, this article not only enriches the theoretical discourse on rural development but also provides a practical framework that can be adapted to university community service programs and broader inter-village development initiatives